2021
DOI: 10.5713/ajas.19.0612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carcass and meat quality traits between lean and fat Pekin ducks

Abstract: According to market demand, meat duck breeding mainly includes 2 breeding directions: lean Pekin duck (LPD) and fat Pekin duck (FPD). The aim of the present study was to compare carcass and meat quality traits between 2 strains, and to provide basic data for guidelines of processing and meat quality improvement. Methods A total of 62 female Pekin ducks (32 LPDs and 30 FPDs) at the age of 42 days were slaughtered. The live body weight and carcass traits were measured and calculated. Physical properties of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In this study, the content of ƩMUFA was the highest in the 5 duck breeds/strains, while previous studies in other duck breeds showed that ƩSFA was the highest ( Chen et al, 2016 ; Franco et al, 2012 ), which may be determined by different breeds/strains, environment, or diet. Further analysis showed that fatty acid composition and content were significantly different among 5 duck breeds/strains, which confirmed the results from a previous study that the breeds/strains had a significant effect on the contents of fatty acids ( Ding et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the content of ƩMUFA was the highest in the 5 duck breeds/strains, while previous studies in other duck breeds showed that ƩSFA was the highest ( Chen et al, 2016 ; Franco et al, 2012 ), which may be determined by different breeds/strains, environment, or diet. Further analysis showed that fatty acid composition and content were significantly different among 5 duck breeds/strains, which confirmed the results from a previous study that the breeds/strains had a significant effect on the contents of fatty acids ( Ding et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Overall, there were significant phenotypic differences between the two populations. Long-term breeding work has resulted in vast differences between the two strains of Pekin ducks (Ding et al 2019).…”
Section: Description Of Traits and Population Structure Analysismentioning
confidence: 99%
“…For more than 30 years in China, selection of the lean-type ducks mainly focused on various carcass traits, including breast muscle yield, feed conversion ratio and growth rate, while in the fat-type ducks, the selection focused on fat traits, including subcutaneous fat ratio and skin thickness. The lean-type ducks mainly provide meat and its byproducts after slaughter, the fat-type ducks are used mainly as raw material for roast duck because of its high subcutaneous fat percentage (Ding et al 2019). After more than 30 years of breeding, the fat Pekin duck has obtained its excellent characteristics of a high percentage of skin and abdominal fat, which is the key element of taste and texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pekin ducks are one of the most popular breeds of waterfowl in the world kept for meat 1 . They are characterized by high growth performance, and there are different strategies for rearing these ducks 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%